Flash Card Berbasis Augmented Reality (AR) untuk Minat Belajar Materi Teks Deskripsi - Syerilla Intan Narisa Ratih; Nur Samsiyah; Apri Kartikasari HS (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning Indonesian, particularly descriptive text material, requires instructional media that can present objects concretely so that students can more easily understand and describe the objects being studied. However, the instructional media used in schools are still predominantly conventional, making them less effective in attracting students' interest in learning. This study aimed to develop an Augmented Reality (AR)-based Flash Card learning media for descriptive text material and to determine its feasibility as a learning medium for fifth-grade elementary school Indonesian language instruction. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research was conducted at SDN Teguhan 3, involving 12 fifth-grade students and one classroom teacher as the research subjects. Data were collected through observations, interviews, documentation, expert validation questionnaires, and teacher and student response questionnaires. The results indicated that the AR-based Flash Card learning media was feasible for use in the learning process. This was evidenced by the media expert validation score of 87.5%, the material expert validation score of 97.5%, and the language expert validation score of 97.5%, all categorized as highly valid. The teacher response score of 98% and the student response score of 97% were also categorized as excellent. Therefore, the AR-based Flash Card learning media is considered feasible and practical for enhancing students' learning interest in descriptive text material for fifth-grade elementary school students.